Systemic Inflammatory Reaction in Patients With Head and Neck Cancer—An Explorative Study - Astradsson, Thorsteinn; Sellberg, Felix; Berglund, David; Ehrsson, Ylva Tiblom; Laurell, Göran Frans Emanuel (Frontiers in Oncology, 2019)
Aim: To assess the longitudinal pattern of pro-inflammatory cytokines and growth factors in serum up to 1 year following treatment for head and neck cancer. Materials and Methods: Patients with newly diagnosed, curable head and neck cancer were included (n = 30). The most common subsite was oropharynx (n = 13) followed by oral cavity (n = 9). Blood was drawn from all patients at regular intervals (before treatment, 7 weeks after the start of the treatment, and at 3 months and 1 year after termination of treatment) and analyzed for cytokines (Il-1β, Il-2, Il-4, Il-5, Il-6, Il-8, Il-10, GM-CSF, TNF-α, and IFN-γ) and growth factors (G-CSF, FGF-2, EGF, and VEGF). Results: The time point of the peak level of pro-inflammatory cytokines was 7 weeks after start of treatment which corresponded for the majority of patients with termination of radiotherapy or chemoradiotherapy. Patients undergoing chemoradiotherapy exhibited a significant increase of IL-1β, IL-6, and IL-10 at 7 weeks as compared to pre-treatment levels. At 1 year after termination of treatment four patients experienced recurrence of disease while 26 patients were considered disease-free. The patients with recurrence had significantly higher levels of IL-1β, IL-6, IL-8, and IL-10 at 7 weeks after the start of treatment than patients without recurrence. Correlated with T stadium patients with T3-T4 had higher levels of IL-1β and IL-8 than patients with T1-T2 7 weeks after the start of treatment. Conclusions: The observed immune response in this explorative study demonstrates that chemoradiotherapy may induce not only a local treatment effect on the immune system but also effects far outside the irradiated field. The result of the study indicates that analysis of a pro-inflammatory panel of cytokines in serum at 7 weeks after the start of treatment could be of prognostic value in patients with head and neck cancer. Further study of a larger cohort could help identify patients at larger risk for recurrent disease with measurements of pro-inflammatory cytokines under and after treatment.